Dual acid-base catalysis with biologically modified graphene oxide: a sustainable route to polyhydroquinolines with antimicrobial properties - Leila Amiri-Zirtol; Hamideh Emtiazi; Seyedeh Narjes Abootalebi; Ahmad Gholami (Scientific Reports)
Abstract This article conducts an in-depth examination of graphene oxide-aspartic acid (GO-As) as a novel bifunctional nano-organocatalyst distinguished by both catalytic and antibacterial properties. The research elucidates the synthesis of GO through Hummer’s method, followed by the covalent attachment of aspartic acid to the surface of GO nanosheets. This innovative approach is particularly notable as it circumvents the use of hazardous chemicals, thereby promoting environmental sustainability. The newly developed catalyst underwent rigorous analysis employing a variety of spectroscopic techniques, including Fourier Transform Infrared (FT-IR) spectroscopy, Energy-Dispersive X-ray Spectroscopy (EDX), mapping, Field Emission Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and Raman spectroscopy. The findings indicate that the catalyst effectively synthesizes polyhydroquinoline derivatives while demonstrating significant stability over multiple reuse cycles, underscoring its potential applicability in organic synthesis. Furthermore, the antibacterial properties of the GO-modified aspartic acid were evaluated against six pathogenic bacterial species. The results reveal substantial antibacterial activity against both Gram-positive and Gram-negative strains, including two antibiotic-resistant bacteria: Methicillin-resistant Staphylococcus aureus (MRSA), Vancomycin-resistant Enterococcus (VRE), thermogravimetric analysis (TGA), and Raman. In conclusion, the investigation of GO-As as a bifunctional heterogeneous nano-organocatalyst represents a promising advancement in the development of environmentally friendly and effective catalysts with noteworthy antibacterial characteristics.